Bond Activation in Iron(II) and Nickel(II) Complexes of Polypodal Phosphanes - Gentschow, Simon-Andreas; Kohl, Stephan W.; Bauer, Walter; Heinemann, Frank Wilhelm; Wiedemann, Dennis; Grohmann, Andreas (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2010)
A pyridine-derived tetraphosphane ligand (donor set: NP(4)) has been found to undergo remarkably specific C P bond cleavage reactions, thereby producing a ligand with an NP(3) donor set. The reaction may be reversed under suitable conditions, with regeneration of the original NP(4) ligand. In order to investigate the mechanism of this reaction, the NP(3) donor ligand C(5)H(3)N[CME(CH(2)PMe(2))(2)][CMe(2)(CH(2)PMe(2))] (11) was prepared, and its iron(II) complex 4 generated from Fe(BF(4))(2) center dot 6H(2)O, with methyl diethylphosphinite (7) as an additional monodentate ligand. Ligand 11 has, in addition to the NP(3) donor set, one methyl group in close contact with the iron center, reminiscent of an agostic M center dot center dot center dot H-C interaction. Depending on the stoichiometric amount of iron(II) salt, a side product 15 is formed, which has a diethylphosphane ligand instead of the phosphinite 7 coordinated to iron(II). While attempts to deprotonate the metal-coordinated methyl group in 4 were unsuccessful, the reaction was shown to occur in an alternative complex (18), which is similar to 4 but has a trimethylphosphane ligand instead of the phosphinite 7. The reaction of complex 15 with CO gave two different products, which were both characterized by single-crystal X-ray diffraction. One (19) is the dicarbonyl iron(II) complex of the triphosphane ligand 11, the other (3) is the carbonyl iron(II) complex of the tetraphosphane C(5)H(3)N[CMe(CH(2)PMe(2))(2)](2) (1). This suggests an intermolecular mechanism for the C-P bond formation in question.
Keywords: Bond Activation; N/P Ligands; Polypodal Ligands; Agostic Interaction; Iron; Nickel